Ready to Reform: How Popular Initiatives Can Be Successful - Katharina Eva Hofer; Christian Marti; Monika Bütler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study whether the number of signatures collected to qualify a popular initiative affects the probability of reforming the status quo. The initiative process is modeled as a sequential game under uncertainty: petitioners make an entry decision and collect signatures to qualify the initiative. Politicians decide about a political compromise - a counter proposal - after which petitioners have the option to withdraw the initiative before the vote. In equilibrium, politicians infer the initiative's popularity from the number of signatures and collection time. They more likely grant counter proposals to initiatives perceived as a threat to the status quo. To prove their success probability, petitioners sometimes have the incentive to collect more signatures than required for qualification. We test model predictions based on the data set of all Swiss constitutional initiatives at federal level between 1891 and 2010. Overall, we find supporting evidence for the model mechanisms. Reforms are most likely once a far-reaching counter proposal is issued such that the initiative is withdrawn. We find a significant effect of collecting more signatures than required on the probability of provoking a compromise.
Keywords: D72; P16; C70; 330